PREWEDDING PHOTO HYPERREALITY IN BALI - Surya Dinata, Ramanda Dimas; Ardika, I Wayan; Darma Putra, I Nyoman; Gde Pujaastawa, Ida Bagus (E-Journal of Cultural Studies, 2022)
The practice of Hindu marriages in Bali has been unknowingly hit by the name pop culture, or in lifestyle terms as pre-wedding photos. The wedding customs of the Hindu community in Bali as a local tradition or local culture that previously did not recognize the term pre-wedding photos began to be inserted and produced through materialistic discourses and practices. Pre-wedding photos encourage the presence of an element of hyperreality from the millennial lifestyle that is mixed by digital and virtual spaces, as a trend of 'futuristic', 'replica', and 'copy' which has actually surpassed reality itself since its presence in 1996. The research is located in Bali and uses qualitative methods. The problems studied include (1) why there is a tendency for hyperreality in pre-wedding photos; (2) what are the forms of hyperreality of pre-wedding photos in Bali; (3) what are the implications of the hyperreality of pre-wedding photos in Bali. In general, this research is to deconstruct what is behind the pre-wedding photo phenomenon and reveal facts that can provide an overview of knowledge and understanding of its relationship with the hyper-reality of pre-wedding photos in Bali. The analysis of this research uses several theories, namely hypersemiotic theory, deconstruction theory, and commodification theory. The results show that (1) the factors that cause hyperreality in pre-wedding photos are lifestyle factors, commercial industry factors, globalization factors, and the factors of negotiation between photographers and clients (brides); (2) forms of hyperreality in pre-wedding photos in Bali show visual engineering, cultural fabrication, love accentuation, hybrid identity, parody and reinterpretation of style; (3) the implications of the hyperreality of pre-wedding photos in Bali show three implications, namely the implications of aesthetic innovation, the implications of an unstable commercial industry, and the implications of shifting meaning. What is presented in the pre-wedding photo phenomenon is a celebration of desire (symbol sales) in various manipulative ways and various supporting media. Keywords: Hyperreality, pre-wedding photos, Hindu community, Bali